Addressing the dichotomy of fishing and climate in fishery management with the FishClim model - Grégory Beaugrand; Alexis Balembois; Loïck Kléparski; Richard R. Kirby (Communications Biology, 2022)
The FishClim model is presented, which quantifies the influence of fishing and climate on fisheries in order to develop strategies for sustainable, long-term, fish stock management.